Platelet transcriptome-based approaches in the fight against dengue and other diseases - Suppiah, Jeyanthi; Syed, Sakinah; Chan, Shie Yien; Wong, Yien Ping; Bala, Jamilu Abubakar; Lawal, Nafi'u; Benelli, Giovanni; Subbiah, Suresh Kumar; Chee, Hui Yee (Universiti Putra Malaysia Press, 2018)
Human platelets are anucleate cells that lack in deoxyribonucleic acid (DNA), thus hampering genomic study on them. However, the presence of their own messenger ribonucleic acid (mRNA) transcript allows functional study via the transcriptome approach. Transcriptome not only allows profiling of platelet but also aids in studying gene regulation in virus infections and other diseases that have an impact on platelets. Some viruses are known to affect the platelet either by causing a reduction or destruction. Dengue virus is one of the most postulated virus having such effect and frequently linked to platelet reduction. The transcriptome approach has a pivotal role in providing a deeper insight to link certain diseases and their effect on platelets. This review critically discusses role of platelet in dengue and other viral diseases of public health relevance, with a specific focus on the methods currently used in platelet transcriptome profiling.